Effects of pre-competitive preparation period on the evolution of isokinetic profile in international professional handball players - Maurelli, O. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Handball is a team sport played between two teams of seven players on an area of 40 m long and 20 m wide, for 2 periods of 30 min. In team sports, such as handball, in order to prepare for the very long period of competition, the pre-competitive preparation period (Pc2P) usually involves the development of technical and tactical qualities and those of all the physical qualities (Seo et al., 2015; Gorostiaga et al., 1999). Given the importance of the lower limb strength in handball, it seems interesting to analyze the influence of the Pc2P on the evolution of isokinetic muscle values (Crosier et al., 2008). Our hypothesis was that Pc2P may increase the maximum strength and power parameters of the flexor (Hamstring - H) and extensor (Quadriceps - Q) muscles of the knee joint. Methods: 19 male handball players, all French or foreign international handball players, belonging to the Ligue 1 club Montpellier Agglomeration Handball (MAHB - France), participated in this study. Pc2P, with a duration of 8 weeks, included three distinct phases. Firstly, a recovery phase of 2 weeks, with 3 sessions of strength training per week, devoted to the lower limbs. Secondly, a phase of 4 weeks, with 2 sessions of lower limb weight training per week. Finally, a final phase of two weeks, with 2 sessions per week. An isokinetic test protocol on dynamometer Biodex System 3® was carried out before and after the Pc2P. The evaluation was performed on the dominant and non-dominant leg in concentric (60°/s and 240°/s) and eccentric (30°/s) modality, in order to determine the peak torque (PT), average power (AP) and ratio, dominant and non-dominant leg (DNDR), agonist/antagonist (AAR) and combined (CR). Results: At 60°/s, in concentric modality, the comparison of PT values, before and after Pc2P, shows no significant difference for Q. For H, we observed a significant increase (p<0.001) of PT on both sides. At 240°/s, in concentric modality, our results showed a significant increase (0.001).